Daily temperature variation lowers the lethal and sublethal impact of a pesticide pulse due to a higher degradation rate. (January 2021) - Delnat, Vienna; Verborgt, Jonathan; Janssens, Lizanne; Stoks, Robby
Abstract: Daily temperature variation (DTV) is an important warming-related stressor that may magnify pesticide toxicity. Yet, it is unknown whether the pesticide impact under DTV is partly ameliorated by a faster pesticide degradation caused by cyclically higher temperatures under DTV. As synergisms may be more likely under energy-limiting conditions, the impact of the pesticide chlorpyrifos was tested under DTV on the mosquito Culex pipiens in the absence and presence of interspecific competition with the water flea Daphnia magna . Chlorpyrifos exposure at a constant temperature without interspecific competition caused considerable mortality, decreased development time, and increased pupal mass of C. pipiens . Competition with D. magna had negative sublethal effects, but it did not affect the toxicity of chlorpyrifos. In contrast, the presence of C. pipiens decreased the impact of chlorpyrifos on D. magna probably due to corporal absorption of chlorpyrifos by C. pipiens . A key finding was that chlorpyrifos no longer caused lethal effects on C. pipiens under DTV, despite DTV on its own being mildly lethal. Additionally, chlorpyrifos exposure under DTV decreased development time less and had no effect anymore on pupal mass compared to chlorpyrifos exposure at a constant temperature. Similarly, the negative chlorpyrifos impact on adult survival of D. magna was less under DTV than at the constant temperature. This could be explained by a faster chlorpyrifos degradation under DTV. This antagonism between pesticide exposure and DTV is likely widespread because organisms experience DTV, many pesticides are applied in pulses, and pesticide degradation is faster at higher temperatures. Highlights: Daily temperature variation (DTV) and competition may affect pesticide impact. Competition had negative sublethal effects but did not increase pesticide impact. DTV increased pesticide degradation and as a result lowered the pesticide impact. Antagonisms between pesticide pulses and DTV may be common in agriculture.